(untitled) (Ameghiniana, 2012)
The sedimentary section at the Quitéria outcrop (Pantano Grande, central portion of Rio Grande do Sul State, Brazil) carries diverse and abundant fossil associations of plants and palynomorphs. This section includes coal deposits of the early Permian Rio Bonito Formation in the Paraná Basin. This contribution presents a taxonomic re-evaluation on paleobotanical records based on an in-depth revisión of available data as well as direct analysis from materials deposited in collections (published and unpublished). A taxonomic list is presented, based on the anlysis of all published data. A stratigraphic framework is offered, showing previous and new records in order to better understand the biostratigraphy of the rocks involved. Accordingt to this re-evaluation, the Quitéria Outcrop carries 14 morphospecies of plant macrofossils —including leaves and seeds of Glossopteridales— constituting a typical coal-forming flora. New palynological data derived from six samples taken in this section reveal diversified and abundant associations, including 29 species of spores, 36 of pollen grains and four taxa related to algae and fungi. Quantitative analysis shows that most samples are closely correlated with the previously known “Lundbladispora-Punctatisporites-Portalites Association”, derived from a hygrophilous environment. The associations are compatible with the Glossopteris-Rhodeopteridium Zone and with the Protohaploxypinus goraiensis Subzone (base of the Vittatina costabilis Zone), related to the Cisuralian (early Permian). Stratigraphical considerations are based on comparision with neighboring sections and on the regional erosional surface recognized in this outcrop. Resumen. PALEOBOTÁNICA Y PALINOLOGÍA DE LA FORMACIÓN RÍO BONITO (PÉRMICO INFERIOR, CUENCA DE PARANÁ, BRASIL) EN EL AFLORAMIENTO QUITÉRIA. La secuencia sedimentaria expuesta en el afloramiento Quitéria (Encruzilhada do Sul, Rio Grande do Sul, Brasil) contiene abundantes y variadas asociaciones palinológicas y restos de plantas fósiles. Esta secuencia es referida a los yacimientos de carbón de la Formación Río Bonito, Pérmico temprano de la Cuenca Paraná. En este trabajo se presenta una nueva evaluación taxonómica de los registros paleobotánicos sobre la base de una revisión exhaustiva de los datos disponibles, así como el análisis directo de los materiales depositados en las colecciones (publicados y no publicados). Una lista taxonómica se presenta con los registros histórico-sistemáticos y el control estratigráfico de cada taxon con el fin de comprender mejor su importancia bioestratigrafía. De acuerdo con esta reevaluación, el afloramiento contiene 14 morfoespecies de macrofósiles vegetales de hojas y semillas de Glossopteridales, constituyendo una flora típica en la formación de carbón. Los nuevos análisis palinológicos de 6 muestras revelaron asociaciones variadas y abundantes, incluyendo 29 especies de esporas, 36 granos de polen y cuatro relacionadas con los elementos algales y hongos. El análisis cuantitativo demuestra que la mayoría de las muestras está estrechamente relacionada con la conocida asociación de “Lundbladispora-Punctatisporites-Portalites, que se describe como de ambiente higrófilo. Las asociaciones son compatibles con la Zona Glossopteris-Rhodeopteridium y la Subzona Protohaploxypinus goraiensis (base de la Zona Vittatina costabilis) del Cisuraliano, Pérmico temprano. Se proporcionan consideraciones estratigráficas sobre la base de comparaciones con las secciones adyacentes, y de la superficie erosiva regional reconocida en el afloramiento.